Analisis Laporan Keuangan Berdasarkan Rasio Profitabilitas Untuk Menilai Kinerja Keuangan UMKM Zieffa Bakery - Layla Nurul Sakinah; Putri Salsa Nabila; Budi Dharma (Universitas Labuhanbatu, 2023)
Financial statements are the final product of an accounting process that functions as a channel of information and communication between internal parties (businesses) and external parties or other parties interested in data or reports from the company's operational operations presented. The financial statements consist of three lists: a balance sheet, an income statement, and a list of retained earnings. Companies need to understand their financial condition and performance in order to survive, develop, and develop. The study tries to determine the exact way in which a proper analysis of the state of the company and financial performance is also required. By utilizing the balance sheet and income statement as financial statements, this study seeks to evaluate the financial performance of Zieffa Bakery's MSMEs. A qualitative descriptive research design was used for this study. Based on the review of the data and the debates that followed, it can be concluded in some respects that Zieffa Bakery's financial performance has produced enough improvement every ratio and every year. Except for 2020, which was prone to fall due to the Covid-19 virus, so sales were significantly reduced.